PENGARUH KONSENTRASI KATALIS DAN REUSABILITY KATALIS PADA SINTESIS TRIASETIN DENGAN KATALISATOR LEWATIT - Lucky Wahyu Nuzulia Setyaningsih; Umi Mei Rizkiyaningrum; Risky Andi (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
Triacetin is a product from reaction between glycerol and acetic acid on acid catalyst. The use of solid catalysts such as ion exchange Lewatit is an alternative method to ease product separation. Synthesize of triacetin was conducted in a batch reactor with stirring speed of 175 rpm, at temperarture of 100oC and the reactant ratio of 6 mole acetic acid / glycerol. The effect of concentration catalyst and reusability of catalyst were investigated. The highest conversion obtained for 84,84 % in catalyst concentration 5% to weight of glycerol. The result showed that comparison of catalyst concentration give real effect to the conversion of glycerol into triacetin, while the reusability catalyst does not give a significant effect on glycerol conversion be triacetin.